(untitled) (Global Journal of Human-Social Science, 2013)
The language which is learned after the learning of native language is called second language and the process of learning the second language is called second language acquisition (Gass & Selinker, 2008). The study of learning strategies has gained much importance in the field of second language acquisition during the past few decades (Koch, 2005). â€œLanguage learning strategies are operations employed by the learner to aid the acquisition, storage, retrieval, and use of information; specific actions taken by the learners to make learning easier, faster, more enjoyable, more self-directed, more effective, and more transferable to new situationsâ€ (Oxford, 1990).